Growing pereskia aculeata under intermittent irrigation according to levels of matric potential reduction - Carla Regina Amorim, Dos Anjos Queiroz; De Andrade, Reginaldo Rodrigues; De Morais, Sérgio Antônio Lemos; Pavani, Luiz Carlos [UNESP] (My University, 2015)
Pereskia aculeata Mill., popularly known in Brazil as “Ora-pro-nobis”, is an unconventional edible vegetable. Taking into account its potential for agronomic cultivation, this study aimed to evaluate the growth response of this plant under intermittent drought through controlled reductions in the substrate matric potential, in a greenhouse. Treatments consisted of adding to the pots a volume of water to raise the matric potential to -5 kPa, according to the water retention curve in the substrate, whenever the mean substrate matric potential reached values between -10 kPa and -70 kPa, depending on the treatment. At 140 days after transplanting, leaf area and dry mass of leaves, stems and roots were determined. The intermittent reduction of the matric potential in the root zone of “Ora-pro-nobis” affected less the dry mass accumulation in leaves (reduction of 21.4%) than in stems (reduction of 48.1%) and roots (reduction of 63.7%), and that is interesting because leaves are the main commercial product of this plant. The treatment also modified the proportionality of dry mass allocation among plant parts and reduced the photosynthetic efficiency of leaves, fact evidenced by the linear increase of the specific leaf area (0.63 cm2 g-1 kPa-1) and leaf area ratio (0.39 cm-2 g-1 kPa-1), although not affecting directly the leaf area.
Keywords: Unconventional edible vegetable; Water deficit; “Ora-pro-nobis”